The Constitutional Implications of the Survival of the Diocese of Sodor and Man. (May 2019) - Edge, Peter W
Abstract : The Lord Bishop of Sodor and Man is an important member of the Legislative Council, the second chamber of the Manx Tynwald. The shape of Tynwald has changed considerably since the mid-nineteenth century, and there have been frequent reviews of the place of ecclesiastical officers in it. The most recent debates illuminate this form of religious representation, but in particular show the importance of ecclesiastical structures – and the contingent status of the Diocese of Sodor and Man – in the lord bishop retaining a vote, as well as a voice, in the principal organ of governance in the Isle of Man. This article argues that a more critical approach is needed in weighing the ecclesiastical structure argument against other constitutional arguments around the constitutional position of the lord bishop.